The Influence of Emotional Intelligence Level, Job Satisfaction and Organizational Culture on Organizational Citizenship Behavior (OCB) of PT. Hilon Medan Employees - M. Nelson Pinem (Journal Boas : Business, Economics, Accounting And Management, 2022)
The formulation of the problem in this research is how the effect of emotional intelligence level, job satisfaction and organizational culture partially or simultaneously toward Organizational Citizenship Behavior (OCB) of PT.Hilon Medan. This research aims to determine and analyze the effect of emotional intelligence level, job satisfaction and organizational culture on Organizational Citizenship Behavior (OCB) of Staff PT.Hilon Medan either partially orsimultaneously The method of analysis used in this research is descriptive data analysis and then emotional analyze by using multiple linier regression. The variables in this emotional analyze by using multiple linier regression. The variables in this emotional analyze by using multiple linier regression. The variables in this emotional analyze by using multiple linier regression. The variables in this emotional analyze by using multiple linier regression. The variables in this